2019
DOI: 10.1002/iid3.248
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the immunological understanding of association between tonsil and immunoglobulin A nephropathy as a tonsil‐induced autoimmune/inflammatory syndrome

Abstract: Introduction Immunoglobulin A nephropathy (IgAN) is the most common form of primary glomerulonephritis worldwide. It is well known that upper respiratory tract infections, particularly acute tonsillitis, often worsen IgAN. Recent many clinical studies clearly show that tonsillectomy with steroid pulse therapy is the effective treatments for IgAN patients. Recently, the immunological evidence of association between tonsil and IgAN has been reported. Methods In this revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 47 publications
0
16
0
2
Order By: Relevance
“…Acute tonsillitis can aggravate IgAN; therefore, the tonsils likely produce the Gd-IgA1 that causes IgAN (30). Double immunostaining showed that the distributions of IgA and Gd-IgA1 were identical in the tonsils and glomeruli, but of the two, serum Gd-IgA1 levels were more representative of the status of IgAN progression.…”
Section: Discussionmentioning
confidence: 96%
“…Acute tonsillitis can aggravate IgAN; therefore, the tonsils likely produce the Gd-IgA1 that causes IgAN (30). Double immunostaining showed that the distributions of IgA and Gd-IgA1 were identical in the tonsils and glomeruli, but of the two, serum Gd-IgA1 levels were more representative of the status of IgAN progression.…”
Section: Discussionmentioning
confidence: 96%
“…Chronic infection has long been considered a risk factor for various disorders including autoimmune diseases, since the era of ancient Mesopotamia and Greece. ( 11 , 12 ) Chronic tonsillitis has been attracting attention as a trigger of many autoimmune diseases such as IgA nephritis, IgA vasculitis, palmoplantar pustulosis, psoriasis, rheumatoid arthritis, Behçet’s disease, and myositis. Tonsillectomy has been used to alleviate these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The following mechanism has been proposed to explain the abnormal immune reaction induced by chronic tonsillitis. ( 12 ) First, indigenous unmethylated bacterial nucleotides hyperactivate immune cells (B cells, T cells, and dendritic cells) that reside in the tonsils through Toll-like receptor 9. Interferon-γ and tumor necrosis factor-α produced by activated T cells reactivate these cells and expand the population of autoreactive T cells and autoantibodies-producing B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Такие же результаты получены в крупном исследовании аналогичного дизайна [49] и метаанализов других контролируемых и ретроспективных исследований, в которых комбинация ТЭ с КС более эффективна в снижении рисков прогрессирования IgAN в сравнении с ИСТ (в основном КС) без ТЭ [44,45,49]. Эти данные позволяют предполагать, что редукция активированных В-клеток, продуцентов Gd-IgA1 и Т-клеток, принимающих непосредственное участие в патогенезе IgAN [50], в результате ТЭ может иметь стратегическое значение в изменении эволюции случаев IgAN с высокой гистологической активностью. В пользу такого предположения свидетельствуют данные повторных биопсий, показавшие более выраженную регрессию воспалительных морфологических изменений у получавших КС в сочетании с ТЭ в отличие от монотерапии КС [19,51].…”
Section: îáñóAeäåíèåunclassified